Use of sodium‐glucose co‐transporter‐2 inhibitors in Asian patients with type 2 diabetes and kidney disease: An Asian perspective and expert recommendations. Issue 2 (20th November 2020) - Khoo, Chin Meng; Deerochanawong, Chaicharn; Chan, Siew Pheng; Matawaran, Bien; Sheu, Wayne Huey‐Herng; Chan, Juliana; Mithal, Ambrish; Luk, Andrea; Suastika, Ketut; Yoon, Kun‐Ho; Ji, Linong; Man, Nguyen Huu; et al.
Abstract: Early onset of type 2 diabetes and a high prevalence of co‐morbidities predispose the Asian population to a high risk for, and rapid progression of, diabetic kidney disease (DKD). Apart from renin‐angiotensin system inhibitors, sodium‐glucose co‐transporter‐2 (SGLT‐2) inhibitors have been shown to delay renal disease progression in patients with DKD. In this review article, we consolidate the existing literature on SGLT‐2 inhibitor use in Asian patients with DKD to establish contemporary guidance for clinicians. We extensively reviewed recommendations from international and regional guidelines, data from studies on Asian patients with DKD, global trials (DAPA‐CKD, CREDENCE and DELIGHT) and cardiovascular outcomes trials. In patients with DKD, SGLT‐2 inhibitor therapy significantly reduced albuminuria and the risk of hard renal outcomes (defined as the onset of end‐stage kidney disease, substantial decline in renal function from baseline and renal death), cardiovascular outcomes and hospitalization for heart failure. In all the cardiovascular and renal outcomes trials, there was an initial decline in the estimated glomerular filtration rate (eGFR), which was followed by a slowing in the decline of renal function compared with that seen with placebo. Despite an attenuation in glucose‐lowering efficacy in patients with low eGFR, there were sustained reductions in body weight and blood pressure, and an increase in haematocrit. Based on the available evidence, we conclude that SGLT‐2 inhibitors represent an evidence‐based therapeutic option for delaying the progression of renal disease in Asian patients with DKD and preserving renal function in patients at high risk of kidney disease.